2010
DOI: 10.1007/s10021-010-9349-y
|View full text |Cite
|
Sign up to set email alerts
|

Field Simulation of Global Change: Transplanting Northern Bog Mesocosms Southward

Abstract: A large proportion of northern peatlands consists of Sphagnum-dominated ombrotrophic bogs. In these bogs, peat mosses (Sphagnum) and vascular plants occur in an apparent stable equilibrium, thereby sustaining the carbon sink function of the bog ecosystem. How global warming and increased nitrogen (N) deposition will affect the species composition in bog vegetation is still unclear. We performed a transplantation experiment in which mesocosms with intact vegetation were transplanted southward from north Sweden … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 51 publications
2
39
1
1
Order By: Relevance
“…The use of soil transplant as a proxy to study the effects of global changes has been successfully demonstrated in both plant biology and microbiology (Balser and Firestone, 2005;Breeuwer et al, 2010;De Frenne et al, 2011;Lazzaro et al, 2011;Vanhala et al, 2011). It was reported that soil microbial community structure and community functions were altered when soil was transplanted into warmer regions to simulate global warming (Vanhala et al, 2011), which was consistent with a number of studies showing that warming altered microbial community (Petchey et al, 1999;Rinnan et al, 2007;Zhou et al, 2012).…”
Section: Introductionsupporting
confidence: 62%
“…The use of soil transplant as a proxy to study the effects of global changes has been successfully demonstrated in both plant biology and microbiology (Balser and Firestone, 2005;Breeuwer et al, 2010;De Frenne et al, 2011;Lazzaro et al, 2011;Vanhala et al, 2011). It was reported that soil microbial community structure and community functions were altered when soil was transplanted into warmer regions to simulate global warming (Vanhala et al, 2011), which was consistent with a number of studies showing that warming altered microbial community (Petchey et al, 1999;Rinnan et al, 2007;Zhou et al, 2012).…”
Section: Introductionsupporting
confidence: 62%
“…Several field experimental approaches have been used to investigate potential effects of global warming on the ecosystem, for example field warming using external heat inputs (Luo et al 2001;Melillo et al 2002), observing differences in ecosystems along natural climatic gradients (Conant et al 2000;Rodeghiero and Cescatti 2005), or transferring ecosystem components to a new site with different climatic conditions (Breeuwer et al 2010;Hart 2006;Link et al 2003;Rey et al 2007). Especially, reciprocal treatment (simulating climate cooling) to that of warming can strengthen the conclusions drawn from warming treatment in which temperature has a dominant effect on soil-plant processes (Hart and Perry 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The main environmental gradients are pH and height above the water table, the latter often dichotomized as hollows (peat surface closer to the water table) and hummocks (peat surface farther above the water table). Not surprisingly, vegetation changes have also been attributed to changes in precipitation and temperature (Belyea and Clymo 2001, Weltzin et al 2003, Gunnarsson and Flodin 2007, Breeuwer et al 2010) and long-term exposure to atmospheric deposition (Gunnarsson et al 2000, Limpens et al 2011. The impact of atmosphere deposition is likely most evident in bogs, as they more heavily rely upon atmospheric fluxes than fens.…”
Section: Introductionmentioning
confidence: 99%